Proximal tibia bone mineral density correlates more closely with hip density in men with knee osteoarthritis - Junya Itou; Ayano Kuwasawa; Kotaro Nihei; Ken Okazaki (Journal of Joint Surgery and Research)
Purpose: Achieving biological fixation of the often loosened tibia is increasingly important for total knee arthroplasty (TKA), with one key factor being the bone density of the proximal tibia. This study examined whether hip bone mineral density (BMD), the most common diagnostic tool for osteoporosis, can estimate tibial BMD in both sexes. Methods: This retrospective study included patients who underwent primary TKA with hip and tibial BMD measurement. Tibial BMD was measured 10 ​mm distal to the lateral tibial articular surface, separately for the medial (BMDm) and lateral (BMDl) sides. Additionally, the association between BMD and lower limb alignment was evaluated. Results: In total, 1012 knees were included (79.3% in women). The mean patient age at surgery was 73.3 ​± ​7.5 years. The mean total hip BMD for women and men was 0.79 ​± ​0.13 ​g/cm2 and 0.95 ​± ​0.16 ​g/cm2, respectively. The mean BMDm and BMDl was, respectively, 0.75 ​± ​0.16 ​g/cm2 and 0.63 ​± ​0.13 ​g/cm2 in women and 0.92 ​± ​0.18 ​g/cm2 and 0.89 ​± ​0.18 ​g/cm2 in men. Both BMDm and BMDl showed a moderate correlation with hip BMD (r ​= ​0.67 and 0.66, respectively) in men. In women, BMDm showed a weak correlation (r ​= ​0.47). Regarding lower limb alignment, BMDm was significantly higher in varus alignment than in neutral or valgus alignment. BMDl did not change with lower limb alignment. Conclusions: BMDm and BMDl were moderately correlated with hip BMD in men, while BMDm showed a low correlation in women.